Comparison of enterovirus detection in cerebrospinal fluid with Bacterial Meningitis Score in children - Pires,Frederico Ribeiro (2017)
ABSTRACT Objective To measure the role of enterovirus detection in cerebrospinal fluid compared with the Bacterial Meningitis Score in children with meningitis. Methods A retrospective cohort based on analysis of medical records of pediatric patients diagnosed as meningitis, seen at a private and tertiary hospital in São Paulo, Brazil, between 2011 and 2014. Excluded were patients with critical illness, purpura, ventricular shunt or recent neurosurgery, immunosuppression, concomitant bacterial infection requiring parenteral antibiotic therapy, and those who received antibiotics 72 hours before lumbar puncture. Results The study included 503 patients. Sixty-four patients were excluded and 94 were not submitted to all tests for analysis. Of the remaining 345 patients, 7 were in the Bacterial Meningitis Group and 338 in the Aseptic Meningitis Group. There was no statistical difference between the groups. In the Bacterial Meningitis Score analysis, of the 338 patients with possible aseptic meningitis (negative cultures), 121 of them had one or more points in the Bacterial Meningitis Score, with sensitivity of 100%, specificity of 64.2%, and negative predictive value of 100%. Of the 121 patients with positive Bacterial Meningitis Score, 71% (86 patients) had a positive enterovirus detection in cerebrospinal fluid. Conclusion Enterovirus detection in cerebrospinal fluid was effective to differentiate bacterial from viral meningitis. When the test was analyzed together with the Bacterial Meningitis Score, specificity was higher when compared to Bacterial Meningitis Score alone.